1999
DOI: 10.1089/acm.1999.5.229
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in Acupuncture and Moxibustion Treatment: A Six-Year Survey at a National Clinic in Japan

Abstract: No serious or severe cases such as pneumothorax, infection, or spinal cord injury were reported by the college preceptors and interns. The results indicate that serious or severe adverse events are rare in standard practice. We suggest that most severe or serious cases of adverse events caused by acupuncture reported in journals are actually cases of negligence. In the future, negligence should be discussed from the point of view of medical education and technical instruction for the therapists, and adverse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 11 publications
4
84
1
4
Order By: Relevance
“…When compared with similar prospective studies on acupuncture, the AE rate of 19.18% reported in this study appears high. Yamashita et al 26 26 AEs were only reported if the practitioner or patient felt it was a problem, which may account for the low rate of AEs in their study (0.14%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…When compared with similar prospective studies on acupuncture, the AE rate of 19.18% reported in this study appears high. Yamashita et al 26 26 AEs were only reported if the practitioner or patient felt it was a problem, which may account for the low rate of AEs in their study (0.14%).…”
Section: Discussionmentioning
confidence: 76%
“…[26][27][28][29][30][31] Results from acupuncture AE studies cannot be extrapolated and applied to TrP-DN as it differs from acupuncture in the points treated and the method and depth of needle stimulation. 27 however the majority of these could be viewed as positive such as feeling relaxed, and feeling energized.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, no complications were encountered, which may be attributable to the acupuncture technique. In a previously reported series of a total of 99,442 acupuncture applications, the complication rate was found to be 0.13%-0.14% (31,32). The most frequently reported complications were dislodgement of the needle, pain, vertigo, nausea and vomiting, bleeding, fever and contact dermatitis (32,33).…”
Section: Discussionmentioning
confidence: 95%
“…Kim et al 13) and Dougherty and Fraser 6) reported spinal epidural hematoma after intraspinal injections of steroids. Also, there have been reports on spinal epidural hematoma after acupunctures 12,28) . The epidural space is an area surrounded by a plexus of epidural veins, which has been historically implicated as the source of epidural hematoma.…”
Section: Discussionmentioning
confidence: 99%